PENGAMATAN FENOLOGI PADA DELAPAN VARIETAS KELAPA SAWIT (Elaeis guineensis Jacq.) MENGGUNAKAN KONSEP THERMAL UNIT - Iput Pradiko; Sujadi Sujadi; Suroso Rahutomo (Pusat Penelitian Kelapa Sawit, 2019)
Plant growth and development depends on environmental conditions (including air temperature). Effect of environmental conditions on plant development and growth is known as phenology. The general concept used to determine the effect of temperature on plant development and growth quantitatively is thermal units. This study was conducted to observe the phenology of eight oil palm varieties released by the Indonesian Palm Oil Research Institute (IOPRI) based on the thermal units concept. This study also explained the implications of the phenology characteristics from each variety in the selection of agro-climate-specific oil palm varieties. The research was conducted at the demonstration plot of Adolina Seed Garden PT. Perkebunan Nusantara IV, Serdang Bedagai Regency, North Sumatra with an altitude of 10 m asl during September 11th, 2014 until June 30th, 2018. The results showed that the appearance of the first leaf until bunch was ripened and harvested from DxP Avros, DyP Dumpy, DxP LaMe, DxP Langkat, DxP PPKS 540, DxP PPKS 718, DxP Simalungun and DxP Yangambi require thermal units (oC days) and duration (days) respectively 5.785 and 457; 5,756 and 454; 6,050 and 476; 5,903 and 467; 5,775 and 452; 6.164 and 484; 6,105 and 478; and 6,084 and 479. DxP PPKS 540 tends to be more suitable for areas with low daily average temperature conditions (18-23oC). In areas with an average temperature of 24-32oC, all oil palm varieties released by IOPRI will grow optimally. Meanwhile, for areas with an average temperature varies between 30-32oC, varieties should be chosen is varieties which potentially produce more bunch such as DxP Avros, DxP LaMe, DxP Langkat, DxP PPKS 540, DxP Simalungun or DxP Yangambi.